Cystic Echinococcosis: Late Rupture and Complication of a Stable Pulmonary Cyst - J Fisher; Y Shargall; S Krajden; F Moid; V Hoffstein (Canadian Respiratory Journal)
Cystic echinococcosis is observed worldwide. Traditional management includes an invasive surgical approach with adjunctive chemotherapy. It has been suggested that observation alone may be appropriate in asymptomatic individuals with stable cysts. A case involving a 38-year-old Peruvian man with an asymptomatic bronchogenic cyst (suspected to be due to echinococcus, but never definitely diagnosed) is presented. The cyst was first noted in 1998, and was followed for 10 years during which time he remained asymptomatic with minimal radiographic change. One year later, in 2009, he presented with acute rupture of the cyst causing empyema. The patient required thoracotomy, decortication and resection of the ruptured cyst. Final pathology showed Echinococcus organisms. The patient responded well to treatment with albendazole and praziquantel, and became completely asymptomatic within six months.